5a+12+9a=2a-4a

Simple and best practice solution for 5a+12+9a=2a-4a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+12+9a=2a-4a equation:


Simplifying
5a + 12 + 9a = 2a + -4a

Reorder the terms:
12 + 5a + 9a = 2a + -4a

Combine like terms: 5a + 9a = 14a
12 + 14a = 2a + -4a

Combine like terms: 2a + -4a = -2a
12 + 14a = -2a

Solving
12 + 14a = -2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
12 + 14a + 2a = -2a + 2a

Combine like terms: 14a + 2a = 16a
12 + 16a = -2a + 2a

Combine like terms: -2a + 2a = 0
12 + 16a = 0

Add '-12' to each side of the equation.
12 + -12 + 16a = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 16a = 0 + -12
16a = 0 + -12

Combine like terms: 0 + -12 = -12
16a = -12

Divide each side by '16'.
a = -0.75

Simplifying
a = -0.75

See similar equations:

| P-412=1329 | | 0.01x+1.2=3.2 | | 16x^2+49=-25 | | T=180-(9x+32) | | 80+5x+y=180 | | x+21=86 | | p+412=1329 | | -9b+8+7=-3b+13 | | 2=3(3n+-5)-10 | | 9x+6=33x-6 | | 4.3(2x-3)+2.8=9.5x-3 | | 3(z-3)=5+4z | | 24=6(x+-6)-x | | 5x+6x-2=20 | | 8x+13+2x+7=180 | | -2.6d-0.49=1.79 | | 2-2-2-2-2-2-2+2+x=3 | | p-400=1230 | | 4x-6x-40=0 | | 2-2-2-2-2-2-2-2-2=2 | | 6n-18=4n | | an=7+(n-1)(7) | | x-13=3x-27 | | X(x+10)=90 | | 0.06(y-9)+0.08y=0.18y-0.2 | | 13x+12=8x+7+4x+14 | | x-54=27 | | 55x+200=20+65x | | lnx=0.375 | | 6x^2+24=25x | | 27=6(9d-8) | | t+400=1230 |

Equations solver categories